Abundance, spatial variation, and sources of rare earth elements in soils around ion-adsorbed rare earth mining areas. (15th November 2022) - Li, Wanshu; Zuo, Yiping; Wang, Lingqing; Wan, Xiaoming; Yang, Jun; Liang, Tao; Song, Hocheol; Weihrauch, Christoph; Rinklebe, Jörg
Abstract: Rare earth elements (REEs) concentrated in soils have attracted increasing attention about their impact on soil health as emerging contaminants. However, the sources of REEs enriched in soils are diverse and need to be further investigated. Here, surface soil samples were collected from southern Jiangxi Province, China. REEs contents and soil physicochemical properties were determined, and cerium (Ce) and europium (Eu) anomalies were calculated. Moreover, we established a model to further identify the main sources of REEs accumulation in the studied soils. Results show that the abundance of soil REEs reveals larger spatial variation, suggesting spatially heterogeneous distribution of REEs. The median content of light REEs in soils (154.5 mg kg −1 ) of the study area was higher than that of heavy REEs and yttrium (35.8 mg kg −1 ). In addition, most of the soil samples present negative Ce anomalies and all the soil samples present negative Eu anomalies implying the combined effect of weathering and potential exogenous inputs on soil REEs. Positive matrix factorization modeling reveals that soil REEs content is primarily influenced by soil parent materials. Potential anthropogenic sources include mining-related leachate, traffic exhaust, and industrial dust. These results demonstrate that the identification of sources of soil REEs is an important starting point for targeted REEs sources management and regulation of excessive and potentially harmful REEs levels in the soil. Graphical abstract: Image 1 Highlights: Characteristic parameters of soil REEs help to identify the source of REEs. Parent material dominates the contents of soil REEs. Multiple anthropogenic sources may affect soil REEs abundance.